Escalating the Spirituality Values Integration into School Curriculum and Holistic Implementation: Strong Leadership Supports - Juharyanto, Juharyanto; binti Syariff M. Fuad, Dayang Rafidah; Rochmawati, Rochmawati; Lesmana, Indra; Fauzan Shobiry, Ahmad Kholish (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This study aims to analyze the strategy of escalating the integration of spiritual values into the curriculum and its holistic implementation through the support of effective principal leadership. This study was conducted qualitatively in four madrasahs, where data collection was carried out through in-depth interviews, non-participant observation, and documentation. The collected data were discussed in FGDs with 144 participants online and offline to ensure their validity. The results of this study include: 1) convergence of opinions among all stakeholders agreed to include and combine four essential spiritual categories, namely tauhid (Oneness of God), akhlak (good morals), Worship, and Jihad (struggle), into the education curriculum, following common beliefs and the results of deliberation; 2) five strategies that are practically implemented into the following holistic and integrative activities, including; (1) establishing a curriculum integration escalation policy; (2) integrated into the implementation of all materials; (3) carried out jointly between schools and parents; (4) controlled administratively through a liaison book and daily pocket book (a'malul yaum); and (5) carried out in various real actions; 3) leaders have a clear vision and are the best role models. This research provides implications about the importance of visionary leaders in strengthening spiritual values in their curriculum in a planned, systematic, and total manner.